Evidence on global medical travel - Ruggeri, Kai; Záliš, Ladislav; Meurice, Christopher R; Hilton, Ian; Ly, Terry-Lisa; Zupan, Zorana; Hinrichs, Saba (Bulletin of the World Health Organization, 2015)
The potential benefits of travelling across national borders to obtain medical treatment include improved care, decreased costs and reduced waiting times. However, medical travel involves additional risks, compared to obtaining treatment domestically. We review the publicly-available evidence on medical travel. We suggest that medical travel needs to be understood in terms of its potential risks and benefits so that it can be evaluated against alternatives by patients who are seeking care. We propose three domains -quality standards, informed decision-making, economic and legal protection - in which better evidence could support the development of medical travel policies.
Keywords: hodnocení rizik; Decision Making; kvalita zdravotní péče; Health Policy; Health Knowledge, Attitudes, Practice; Global Health; Medical Tourism; zdraví - znalosti, postoje, praxe; celosvětové zdraví; rozhodování; zdravotní turistika; Humans; lidé; Risk Assessment; zdravotní politika; Quality of Health Care